Cartographies of Friendship, Desire, and Home; Notes on surviving neoliberal security regimes - DasGupta, Debanuj (Disability Studies Quarterly, 2014)
In this auto-ethnographic essay I shed light upon processes of racialiazation and sexualization which work to construct the figure of the disabled, diseased, alien. The paper argues disability based immigration policies, along with neoliberal notions of productivity and enterprise operate as technologies of power, excluding queer HiV positive migrant subjects from the gates of the US nation-state. I shed light upon HIV based immigration policies, disability and sexuality rights activism, pre and post 9/11 US national security practices by retracing lived experiences of mine from Kolkata, India and post 9/11 New York City. The narrative journeys to spaces such as HIV clinics, S&M chambers, and hospital rooms in hopes of understanding collective claims to life being made by those occupying the interstitial shadow spaces between nation-states, perverse/ normal, ability/disability, and ultimately life/death.